2021
DOI: 10.1016/j.ophtha.2020.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Prevalence of Myopia among Taiwanese Schoolchildren

Abstract: The aim of this study was to evaluate the changes in the prevalence of myopia in Taiwanese schoolchildren over the past few decades and to analyze the risk factors for myopia.Design: Analysis of 8 consecutive population-based myopia surveys conducted from 1983 through 2017.Participants: An average of 8917 (5019e11 656) schoolchildren 3 to 18 years of age were selected using stratified systematic cluster sampling or by probability proportional to size sampling.Methods: All participants underwent complete ophtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
3
20

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 40 publications
9
79
3
20
Order By: Relevance
“…3 Similar impacts of educational policy changes on myopia have been documented in Singapore and Taiwan. 37,38 The quantitative technique of regression discontinuity analysis can be applied to data of this kind, and a recent study has examined the impact of increasing the mandatory length of schooling on development of myopia in the United Kingdom. 39 This policy resulted in a marked decrease in mean SER.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Similar impacts of educational policy changes on myopia have been documented in Singapore and Taiwan. 37,38 The quantitative technique of regression discontinuity analysis can be applied to data of this kind, and a recent study has examined the impact of increasing the mandatory length of schooling on development of myopia in the United Kingdom. 39 This policy resulted in a marked decrease in mean SER.…”
Section: Educationmentioning
confidence: 99%
“…The evidence is equivocal as to whether recent increases in the use of digital devices are associated with increases in the prevalence of myopia. Data from Taiwan suggest that there has been a steady increase in the prevalence of myopia in very recent years, 38 particularly in younger children, which could be attributed to increasing screen time. This is not inconsistent with the more recent decreases reported after the introduction of increased time outdoors in schools.…”
Section: Use Of Computers and Smart Phonesmentioning
confidence: 99%
“…In Taiwan, by 6 year-old, the prevalence of myopia in preschool children was 12.2%, higher than the other countries 21 . The myopic prevalence of 7-year-old school children increased to 25.41% in 2017 22 . Almost all the myopic population in this age was referred to ophthalmologist for medical intervention in Taiwan 23 .…”
Section: Discussionmentioning
confidence: 97%
“…As of 2016, 90.34% (95% CI, 87.69%e92.99%) and 24.16% (95% CI, 22.20%e26.12%) of 18-year-olds were myopic and highly myopic, respectively. 47 This contrasts with trends in Hong Kong, which has the highest rates of myopia in China, where the prevalence of pediatric myopia has not changed significantly compared with 15 years ago. 48 An analysis of Australian school-aged children in Sydney provided insight on the interplay of race and environment in myopia prevalence trends.…”
Section: Epidemiologic Features Of Myopia Globallymentioning
confidence: 91%
“…46 A review of 5 nationwide surveys from Taiwan between 1983 and 2000 found a trend toward individuals becoming myopic at an earlier age, with an average age of 11 years in 1983 compared with an average age of 8 years by 2000. 28 Tsai et al 47 showed that the prevalence of myopia (at least e0.25 D) and high myopia (at least e6.00 D) increased between 1983 and 2016 in school-aged Taiwanese children. Among 12-year-olds, myopia prevalence increased from 30.7% (95% CI, 26.9%e34.4%) to 76.7% (95% CI, 72.9%e80.4%; P ¼ 0.001), and high myopia prevalence increased from 1.39% (95% CI, 0.4%e2.4%) to 4.26% (95% CI, 3.4%e5.2%; P ¼ 0.008).…”
Section: Epidemiologic Features Of Myopia Globallymentioning
confidence: 99%